Comparative modeling of Bronze Age land use in the Malatya Plain (Turkey). (15th March 2016) - Arıkan, Bülent; Restelli, Francesca Balossi; Masi, Alessia
Abstract: Computational modeling in archeology has proven to be a useful tool in quantifying changes in the paleoenvironment. This especially useful method combines data from diverse disciplines to answer questions focusing on the complex and non-linear aspects of human-environment interactions. The research presented here uses various proxy records to compare the changes in climate during the Bronze Age in the Malatya Plain in eastern Anatolia, which is situated at the northern extremity of northern Mesopotamia. Extensive agropastoral land use modeling was applied to three sites of different size and function in the Malatya Plain during the Early Bronze Age I period to simulate the varying scale and intensity of human impacts in relation to changes in the level of social organization, demography, and temporal length. The results suggest that even in land use types subjected to a light footprint, the scale and intensity of anthropogenic impacts change significantly in relation to the level of social organization. Highlights: Modeling is a powerful and analytical tool for archaeological research. The Landscape Evolution model offers high-resolution testing of hypotheses related to long-term surface processes. The Extensive Agropastoral Land Use model allows us to quantify anthropogenic impacts at a given site. Through simulations, sizes of different function and size can be used to assess hypotheses related to human-environment interactions. Such experiments contribute to our understanding of coupled systems research.